Reduction of inflammatory responses by l-serine treatment leads to neuroprotection in mice after traumatic brain injury. (August 2015) - Zhai, Pei-Pei; Xu, Li-Hua; Yang, Juan-Juan; Jiang, Zheng-Lin; Zhao, Guang-Wei; Sun, Li; Wang, Guo-Hua; Li, Xia
Abstract: This study was designed to evaluate the neuroprotective effect ofl -serine and the underlying mechanisms in mice after traumatic brain injury (TBI) induced using a weight drop model. The mice were intraperitoneally injected withl -serine 3 h after TBI and then injected twice each day for 7 days or until the end of the experiment. The neurological severity score, brain water content, lesion volume, and neurone loss were determined. The levels of TNF-α, IL-1β, IL-6, and IL-10 and the number of GFAP- and Iba-1-positive cells and activated caspase-3-positive neurones in the brain tissue ipsilateral to TBI were also measured. Simultaneously, the influences ofl -serine on these variables were observed. In addition, the expression of glycine receptors andl -serine-induced currents were measured. We foundl -serine treatment: 1) decreased the neurological deficit score, brain water content, lesion volume, and neurone loss; 2) inhibited activated caspase-3; and 3) reduced the levels of TNF-α, IL-1β and IL-6 and the number of GFAP- and Iba-1-positive cells. The effects ofl -serine were antagonised by the administration of strychnine, an antagonist of glycine receptors. In addition, we found that glycine receptors were expressed mainly in the cortical neurones but less in the astrocytes or microglial cells, andl -serine activated these receptors and induced strychnine-sensitive currents in these neurones. In conclusion, l -serine induces the activation of glycine receptors, which alleviates neuronal excitotoxicity, a secondary brain injury process, thereby reduces the activation of astrocytes and microglial cells and secretion of proinflammatory cytokines and inhibits neuronal apoptosis. Thus, l -serine treatment leads to neuroprotection of brain tissue through reducing inflammatory responses and improves recovery of the neurological functions in mice after traumatic brain injury. Graphical abstract: Highlights: l -serine was found to be neuroprotective in mice following traumatic brain injury. l -serine treatment reduced brain injury and ameliorated the neurological functions. l -serine treatment inhibited the inflammatory responses. l -serine activated strychnine-sensitive glycine receptors in neurones. Effects ofl -serine were inhibited by strychnine, an antagonist of glycine receptors.